1977
DOI: 10.1088/0022-3719/10/19/024
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance and electroreflectance of TiO2single crystals. II. Assignment to electronic energy levels

Abstract: For pt.I see ibid., vol.10, no.19, p.3893 (1977). The interband optical properties of TiO2 are analysed on the basis of a tight-binding band structure which is calculated by using estimated values for the LCOAO parameters. The major interband transitions giving rise to the pronounced optical structure around 4 eV occur between energy band regions near the Sigma symmetry line of the Brillouin zone. The broad structure of the electroreflectance (ER) is mainly caused by the energy shift of these bands due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
9

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 52 publications
5
20
0
9
Order By: Relevance
“…Transverse and optical phonons determine the lower optical edge observed in experiments. 40,54,55,69 Direct transitions have been observed 45,69 at 3.57 eV for the in-plane directions, in quite good agreement with our estimation for the first bright exciton ͑3.59 eV͒.…”
Section: Analysis Of Excitonic Transitionssupporting
confidence: 86%
See 1 more Smart Citation
“…Transverse and optical phonons determine the lower optical edge observed in experiments. 40,54,55,69 Direct transitions have been observed 45,69 at 3.57 eV for the in-plane directions, in quite good agreement with our estimation for the first bright exciton ͑3.59 eV͒.…”
Section: Analysis Of Excitonic Transitionssupporting
confidence: 86%
“…40͒ and, according to the combined results of absorption, photoluminescence, and Raman-scattering techniques 40 a direct exciton is reported at 3.57 eV. 40,45,69 The absorption edge of 3.2 eV ͑Refs. 56 and 57͒ in anatase is also due to indirect transitions.…”
Section: Introductionmentioning
confidence: 97%
“…There exists, however, few previous works on solids where practical measurements and corresponding analysis are performed on PSXRS. 19 TiO 2 is a representative of a 3d 0 system, and the character of the electronic states near the energy gap has long been discussed in terms of both delocalized [20][21][22][23][24][25][26] and localized [27][28][29][30][31][32] description. Butorin et al measured Ti 2p SXRS of FeTiO 3 and found a broad Raman structure around 3-10 eV and a weak Raman peak at 14 eV below recombination peaks.…”
Section: Introductionmentioning
confidence: 99%
“…In oxides with Al 2 O 3 -type hexagonal structure or TiO 2 -type tetragonal structure there are different bond lengths and different distances between oxygen atoms. For example, in TiO 2 (rutile) the shortest distance between oxygen atoms is d = 0.252 nm (Vos, 1977;Meogher & Lager, 1979), whereas in SiO 2 (quartz) d= 0.260 nm, and in its high-pressure form d= 0.216 nm ( Shannon & Prewitt, 1969, 1976. Furthermore, in Ti 2 O 3 d= 0.279 nm (Rice & Robinson, 1977), V 2 O 3 d = 0.279 nm (Robinson, 1975), Fe 2 O 3 d = 0.262 nm (Newnham &Haan, 1962), and in α -Al 2 O 3 d= 0.252 nm (Shannon & Prewitt, 1969).…”
Section: Distances Between Oxygen Ions In Oxidesmentioning
confidence: 99%